In vitro assessment of antimicrobial, anti-inflammatory, and schistolarvicidal activity of macroalgae-based gold nanoparticles - Kamal, Marwa; Abdel-Raouf, Neveen; Sonbol, Hana; Abdel-Tawab, Heba; Abdelhameed, Mohamed Sayed; Hammouda, Ola; Elsayed, Khaled N. M. (Frontiers in Marine Science, 2022)
There is a growing need to improve facile, eco-friendly, and cheap approaches for nanoparticle synthesis. Green protocols have been investigated for fabrication of nanoparticles using several natural sources as plants, algae, fungi and bacteria. Thus the present study proposed a rapid, convenient, and efficient biosynthesis of gold nanoparticles (Au-NPs) using ethanolic extracts of three macroalgae: Cystoseira myrica, Cystoseira trinodis, and Caulerpa prolifera. The reduction of gold ions and the fabrication of Au-NPs were validated using Ultraviolet-visible (UV–Vis) spectroscopy, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Transmission electron microscopy (TEM) and zeta potential analysis. The produced Au-NPs were tested for their antimicrobial (antibacterial and antifungal), anti-inflammatory and schistolarvicidal activity. Results revealed formation of Au-NPs with average size 12.6 to 15.5 nm and different shapes mainly spherical with pure crystalline nature. Strong antibacterial activity against E. coli (inhibition zones 22 and 19 mm) was recorded by C. myrica and C. trinods based Au-NPs respectively followed by (inhibition zones 20.5 and 18 mm) using C. trinodis and C. myrica based Au-NPs respectively against Staphylococcus aureus. High antifungal activity of C. trinodis and C. myrica based Au-NPs (inhibition zones 18 and 17mm) against Aspergillus niger, Alternaria alternate respectively, followed by inhibition zone (16 mm) using C. trinodis Au-NPs against Candida albicans. Regarding anti-inflammatory and schistolarvicidal activity, Au-NPs fabricated using C. myrica offered 64.2±1.27% inhibitory potential on protein denaturation and recorded the highest schistolarvicidal activity as all Schistosoma mansoni cercariae sank and died after 7 min. These findings proved that macroalgal ethanolic extracts can be used effectively for biosynthesis of Au-NPs. These Au-NPs offer significant alternative antimicrobial, anti-inflammatory and schistolarvicidal agent for biomedical uses.